2015
DOI: 10.1371/journal.pone.0117128
|View full text |Cite
|
Sign up to set email alerts
|

Menthol Attenuates Respiratory Irritation and Elevates Blood Cotinine in Cigarette Smoke Exposed Mice

Abstract: Addition of menthol to cigarettes may be associated with increased initiation of smoking. The potential mechanisms underlying this association are not known. Menthol, likely due to its effects on cold-sensing peripheral sensory neurons, is known to inhibit the sensation of irritation elicited by respiratory irritants. However, it remains unclear whether menthol modulates cigarette smoke irritancy and nicotine absorption during initial exposures to cigarettes, thereby facilitating smoking initiation. Using plet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 49 publications
0
60
0
Order By: Relevance
“…21,22 Evidence from the studies in mice also indicate that menthol's inhibitory effects depend upon TRPM8, which has been shown to underlie the analgesic effects of cold on acute and inflammatory pain via an opioid-dependent central neural pathway. 49 An analgesic action of menthol via a central neural mechanism raises the possibility that menthol stimulation in both the upper and lower airways may contribute to reducing the sensory irritation of nicotine that is sensed most acutely in the throat and lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Evidence from the studies in mice also indicate that menthol's inhibitory effects depend upon TRPM8, which has been shown to underlie the analgesic effects of cold on acute and inflammatory pain via an opioid-dependent central neural pathway. 49 An analgesic action of menthol via a central neural mechanism raises the possibility that menthol stimulation in both the upper and lower airways may contribute to reducing the sensory irritation of nicotine that is sensed most acutely in the throat and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a recent study of menthol cigarettes concluded there was no consistent effect of menthol on perceived harshness and overall impact, 20 whereas a previous study indicated that menthol could either increase or decrease the perceived harshness of a cigarette depending on nicotine concentration. 8 Studies in mice 21,22 indicate that menthol can reduce the sensory irritation from constituents of cigarette smoke, including nicotine, that stimulate the pain receptor TRPA1, 23,24 which has been shown to play a role in cough. 25 However, the numerous other chemical and particulate irritants in tobacco smoke 5,26 have precluded direct measurement of the effect of menthol on the perception of nicotine irritation alone.…”
Section: Introductionmentioning
confidence: 99%
“…7 Together these data suggested that menthol may facilitate smoking initiation by reducing aversion to noxious smoke. [6][7][8] It is currently controversial whether menthol's counterirritant activity extends to oral nicotine and its aversive effects. Most studies examining the effects of menthol in the context of tobacco use were performed in chronic smokers and provide no information about menthol's behavioural effects during initiation of tobacco use.…”
Section: Introductionmentioning
confidence: 88%
“…Higher levels of cotinine were detected in the mice inhaling mentholated cigarette smoke than in the mice inhaling non-mentholated smoke, implying that menthol increases nicotine uptake. 7 These effects were observed at menthol levels present in smoke of commercial menthol cigarettes. 7 Together these data suggested that menthol may facilitate smoking initiation by reducing aversion to noxious smoke.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation